Colored plastic pulp as a collage medium in improving early childhood development - Yetty Trisnayanti; Dwi Nomi Pura (LPPM Universitas Pahlawan Tuanku Tambusai, 2018)
One development that must be considered in the growth of early childhood is motor development, namely fine and rough motor. The problem raised in this study is the lack of fine motor skills in children due to creativity in making learning media still very weak and conventional learning. The purpose of this study was to prove the increase in fine motor skills of early childhood through a colored plastic pulp collage medium. The selection of used materials for colored plastic powder is one way to utilize used material to be recycled and used as a new medium that is attractive to children in making collages to improve fine motor. This research was conducted using 2 cycles of classroom action research. The results showed an increase in fine motor skills of early childhood from undeveloped criteria, began to develop, developed according to expectations to develop very well at the stage of giving glue to the media, arranging colored plastic powder, and tidying the patterns that had been prepared